2022
DOI: 10.29140/ajal.v5n3.53si3
|View full text |Cite
|
Sign up to set email alerts
|

Online machine translation for L2 writing across languages and proficiency levels

Abstract: Using machine translation (MT) tools for language learning has become a common practice among language students in recent years. Studies have investigated how students use MT, how students and teachers perceive its benefits and drawbacks and how helpful it is for language learning. These studies indicate that students think MT tools are helpful in L2 writing due to their quick and easy access and use them in many aspects of L2 writing, such as vocabulary search, grammar checking, and writing revisions. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…However, risks such as accepting incorrect output as correct have also been documented (Loock et al, 2022) and many educators fear misuse (Ohashi, 2022). Despite this, some studies have shown students tend to use machine translation tools, such as Google Translate, constructively in writing rather than avoiding writing itself (Alm & Watanabe, 2022). The emergence of ChatGPT and other advanced generative AI tools has amplified concerns and introduced new ones about plagiarism, originality and depth in student writing (Alshater, 2022;Haque et al, 2022;Roe & Perkins, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, risks such as accepting incorrect output as correct have also been documented (Loock et al, 2022) and many educators fear misuse (Ohashi, 2022). Despite this, some studies have shown students tend to use machine translation tools, such as Google Translate, constructively in writing rather than avoiding writing itself (Alm & Watanabe, 2022). The emergence of ChatGPT and other advanced generative AI tools has amplified concerns and introduced new ones about plagiarism, originality and depth in student writing (Alshater, 2022;Haque et al, 2022;Roe & Perkins, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Building on our previous work (Alm & Watanabe, 2022), which revealed proficient MTT use among advanced language learners, this study further explores advanced students' experiences with MTTs. That research found…”
Section: Introductionmentioning
confidence: 98%
“…Building on our previous work (Alm & Watanabe, 2022), which revealed proficient MTT use among advanced language learners, this study further explores advanced students' experiences with MTTs. That research found Machine translation in language education -Perspectives from advanced language learners 2023, Editorial Universitat Politècnica de València students valued the convenience and guidance MTTs provided for writing, but also recognised the importance of critically evaluating output and avoiding over-reliance on MTTs.…”
Section: Introductionmentioning
confidence: 98%